造血幹細胞移植患者の移植前後の身体機能に関する研究 - 森下 慎一郎; 島田 真一; 眞渕 敏; 田中 隆史; 梶原 和久; 児玉 典彦; 海田 勝仁; 小川 啓恭; 道免 和久 (理学療法学, 2009)
Purpose: In this study, we examined the effects of approximately 5 weeks of rehabilitation, conducted in a clean room, on the physical fitness and quality of life (QOL) of patients who underwent hematopoietic stem cell transplantation (HSCT). Methods: The subjects were 18 patients (11 males, 7 females) 26 to 66 years of age (mean age 48.6 years) who had undergone allogeneic HSCT. Before and after transplantation, muscle strength (grip and quadriceps). six-minute-walk distance (6MWD), number of steps, health-related QOL (SF-36), and weight were evaluated. The rehabilitation program included stretching, muscle strengthening and gait training during the patients' stay in the clean room. Results: Eleven patients completed our rehabilitation program, and 7 patients dropped out. Among the group that completed training, there was a significant decrease in muscle strength and weight after transplantation (p < 0.05). However, 6MWD and number of steps were not decreased after transplantation. Five out of 11 patients showed an increase in 6MWD, and 8 out of 11 patients showed an increase in the number of steps. Two out of 8 QOL items (physical functioning and social functioning) were significantly decreased after transplantation (p < 0.05). Conclusions: Compared with recent studies, our program may be more useful to prevent patients from decreasing of physical fitness and reduced QOL, who underwent HSCT in a clean room. 【目的】造血幹細胞移植患者に対し移植前後約5週間の無菌室入室中に運動療法プログラムを実施した場合の身体機能とQOLに及ぼす影響を調査した。【対象と方法】造血幹細胞移植を受けた患者18名（男11名，女7名：平均年齢48.6 ± 12.8歳）である。評価は握力，膝伸展筋力，6分間歩行距離，1日の歩数，体重，QOL（SF-36）について移植前後で実施した。無菌室内での運動療法はストレッチング，筋力増強運動，歩行練習を実施した。【結果】プログラム完遂者は11名，脱落者は7名であった。完遂群の11例において，移植前に比べ移植後の握力，膝伸展筋力，体重は有意な低下を示した（p < 0.05）。しかし，6分間歩行距離，歩数の有意な減少はなく，11名中5名は6分間歩行距離が向上傾向を示し，11名中8名は歩数が増大傾向を示した。QOLは8項目中2項目（身体機能・社会生活機能）で有意な低下を認めた（p < 0.05）。【結論】無菌室において我々の運動療法プログラムを実施した場合，筋力低下の程度は過去の報告ほどではなく，全身持久性は維持でき，QOL低下は2項目にとどまった。従って，無菌室における我々の運動療法プログラムは有用と考えられた。